2021
DOI: 10.1111/ene.14939
|View full text |Cite
|
Sign up to set email alerts
|

High‐density lipoprotein cholesterol and brain aging amongst rural‐dwelling older adults: a population‐based magnetic resonance imaging study

Abstract: Background and purpose: Current evidence supports the involvement of lipids in brain aging. A range of serum lipids is explored in association with brain structure and cognitive function amongst rural-dwelling older adults. Methods: This population-based cross-sectional study included 184 rural-dwelling adults (age ≥ 65 years, 39.1% women) in Shandong, China. In 2014-2016, data on demographics, lifestyle, health conditions and serum lipids were collected. Volumes of gray matter, white matter, ventricles, hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…6–8. 1758 An additional 14 studies were excluded from the meta-analyses as they were repeated publications from the same cohort (n = 8); without complete data for meta-analysis (n = 4); and with unclear results reporting (n = 2). For multiple publications from the same cohort, we selected a representative study from each cohort based on the following: a greater number of cSVD markers reported, preference for more recent publications, and larger sample size.…”
Section: Resultsmentioning
confidence: 99%
“…6–8. 1758 An additional 14 studies were excluded from the meta-analyses as they were repeated publications from the same cohort (n = 8); without complete data for meta-analysis (n = 4); and with unclear results reporting (n = 2). For multiple publications from the same cohort, we selected a representative study from each cohort based on the following: a greater number of cSVD markers reported, preference for more recent publications, and larger sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Our study did not support a significant mediation effect of Aβ deposits in the associations between serum HDL-C and MDAS, while the t-Tau, Aβ 40 /t-Tau ratios, and Aβ 40 /p-Tau ratios play full mediators on the relationship between HDL-C and MDAS. A study of older adults in China’s rural area showed that low HDL-C is associated with structural brain aging and cognitive dysfunction, but the association of low HDL-C with cognitive aging is not mediated by brain structure ( 44 ). Our data agree with previous research that low HDL-C is associated with cognitive impairment and dementia and is a risk factor for memory deficit and decline ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was a population-based cross-sectional study. Study participants were derived from the Shandong Yanggu Study of Aging and Dementia (SYS-AD) that engaged people who were aged 60 years and older and living in the rural area of Yanlou Town, Yanggu County, western Shandong Province, China, as previously reported [12,16]. Briefly, the baseline examination of the SYS-AD project consisted of a two-phase procedure.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…At phase I, we collected data through face-toface interviews, clinical examinations, and laboratory tests. Data included demographics (e.g., age, sex, early-life education, and adulthood occupation and marital status), lifestyles (e.g., smoking, alcohol intake, and late-life physical and social activity), health conditions (e.g., hypertension, diabetes, hyperlipidemia, stroke, and coronary artery disease), and cognitive performance (e.g., MMSE score and AD8 score) [12,16]. The Social Support Rating Scale, developed and validated among Chinese older adults, was used to assess social contact and support [19].…”
Section: Data Collection and Assessmentmentioning
confidence: 99%
See 1 more Smart Citation